Treatment of Vertigo with a Homeopathic Complex Remedy Compared with Usual Treatments - Schneider, Berthold; Klein, Peter; Weiser, Michael (Arzneimittelforschung, 2005)
The increasing interest in alternative medical practices has led to a number of controlled studies on herbal and homeopathic agents. This paper presents the results of a meta-analysis of four recent clinical trials evaluating the homeopathic preparation Vertigoheell (VH) compared with usual therapies (be-tahistine, Ginkgo biloba extract, di-menhydrinate) for vertigo in a total of 1388 patients. Two trials were observational studies and the other two were randomised double-blind controlled trials. The duration of treatment (6–8 weeks) and dosage were comparable in all studies. Treatments were evaluated for the variables “number of vertigo episodes”, “intensity of episodes” and “duration of episodes”. As the studies differed in the age of patients and in the baseline values of vertigo, the individual reductions of number, intensity and duration of episodes were adjusted on equal age and baseline values (total means). An analysis of variance (with studies as random effects) showed no relevant influence of studies on the adjusted reductions and no relevant interaction between studies and treatment effects. The meta-analysis of all four trials showed equivalent reductions with VH and with control treatment: mean reduction of the number of daily episodes 4.0 for VH and 3.9 for control (standard error 0.11 for both groups); mean reduction of the duration (on a scale 0–4) for VH 1.1 and for the control 1.0 (standard error 0.03 for both groups); mean reduction of the intensity (on a scale 0–4) for VH 1.8 and for the control 1.8 (standard error 0.03 for both groups). In the non-inferiority analysis from all trials, VH was non-inferior in all variables. The results show the applicability of meta-analyses on the data from studies with homeopathic drugs and support the results from the individual studies indicating good efficacy and tolerability of VH in patients with vertigo.
Keywords: Homeopathy; Vertigo; Vertigoheel®, efficacy, meta-analysis, tolerability